Detection of integrons class 1 and class 2 in VTEC strains isolated from pigs - Colello, Rocío (2012)
Introduction and objectives: In the last 10 years, approximately 500 HUS new annual cases w ere reported in Argentina, w ith an incidence of 17/100,000 children under five years old. The production of VT1, VT2 and/or their variants is the primary virulence trait responsible for human disease. VT2e is typically associated w ith pig edema disease and has been detected only rarely in VTEC of human origin. Some studies have show n that VTEC serotypes have developed resistance to antibiotics used in human and veterinary medicine. Humans may obtain antibiotic-resistant E. coli by contact with animals, foods, or environment. The w idespread use of antibiotics creates a reservoir of resistant bacteria carrying antibiotic resistance genes. Integrons contain the genetic determinants of the components of a site-specific recombination system w hich recognize and capture the mobile antibiotic-resistance genes cassette. Integrons include a gene for an integrase (int), an adjacent recombination site (attl), and a strong promoter/s that ensure expression of the integrated cassettes.The aim of this study w as to detect integrons in VTEC strains with antibiotic multiresistance. Material & Methods: Tw enty-one VTEC strains isolated from pig faeces f rom ten farms (named A to J) f rom Argentina w ere analysed to detect integrons (int1 and int2) by PCR. Results: Out of tw enty-one analysed strains, 8 (38 %) carried integrons enconding genes. These strains belonged to 4 different farms. Conclusions: The use of antibiotics in animal production systems has determined that bacteria could develop resistance mechanisms originating strains w ith risk for human if entering a food chain. Integrons are not only associated w ith resistance to antibiotics, but also w ith the horizontal transference of resistance genes. Some studies have informed of the presence of integrons in Enterobacteriaceae and Escherichia coli in samples isolated f rom pigs, not being registered data in VTEC strains so far. In this study integrons class 1 and class 2 w ere detected in VTEC strains isolated from pigs show ing that inadequate use of antibiotic as therapeutic agents or grow ing promoter in veterinary, implies a risk for public health because the acquisition and the horizontal transference of integrons among strains.